Green technology book 2022 : executive summary. (WIPO publication ;, 2022)
The Green Technology Book puts innovation, technology and intellectual property at the forefront in the fight against climate change. This inaugural edition focuses on three important areas: agriculture and forestry, water and coastal regions, and cities, showcasing 200 available solutions that aim to reduce vulnerability and increase resilience to climate impacts.